Electrokinetic response of solid-liquid mixture during filtration and expression - Sadai, Haruna; Shimoizu, Kazuya; Iwasaki, Tomohiro; Yabuta, Nobuyasu; Jami, Mohammed Saedi; Iwata, Masashi (2018)
Expression is one of the solid-liquid separation methods widely used in many practical fields such as food, fermentation, chemical industries and various wastewater treatments. When a slurry material is expressed, the expression process is divided into two periods, filtration period and consolidation period. It is essential to determine the transition point from the filtration to consolidation period for effective operation. In the filter press which is a solid-liquid separation apparatus, the losses of work time and product recovery frequently occur by missing the optimal switching time from the filtration process to compression process. If we can monitor the state of the cake formation in the filter chamber and determine the transition point correctly between the two periods, it is possible to reduce such losses and improve the production efficiency. However, currently a simple and practical determination method for this transition does not exist. In this study, “monitoring of the expression process” was discussed from the electrokinetic point of view; the time course of electric potential difference between filter media has been measured.